P81 The impact of musculoskeletal ultrasound on the referral of patients with suspected inflammatory arthritis from primary care. (20th April 2020) - Baker, Kenneth F; Fatone, Eliana; Hamilton, Jennifer
Abstract: Background: Musculoskeletal ultrasound (MSUS) is a helpful adjunct to clinical history and examination in the assessment of patients with suspected early inflammatory arthritis (EIA). Whereas MSUS is used widely by rheumatologists, data regarding the extent to which general practitioners (GPs) utilise MSUS in the assessment of patients with suspected EIA remain lacking. In this service evaluation, we aimed to quantify the MSUS workload originating from primary care, and its impact on the referral pathway of patients with suspected EIA. Methods: We studied all patients ≥16 years of age who had an MSUS of the hands and wrists performed by the radiology department at the Queen Elizabeth Hospital (Gateshead, UK) between 1st January and 31st December 2018, and where the scan request originated from a GP within primary care. Electronic records were retrospectively reviewed to ascertain the scan request clinical details, radiology report, and subsequent referral of the patient for rheumatology review. The study was registered with the Trust Clinical Improvement Office. Results: 189 patients were scanned: 137 (72%) female, median (IQR, range) age 56 (43-65, 16-91) years. Ultrasonographic abnormalities (synovial hypertrophy, synovitis and/or tenosynovitis) were observed in 31/87 (36%) of suspected EIA patients, and 22/102 (22%) patients without suspicion of EIA, with subsequent referral to rheumatology in 24 and 4 cases from each group respectively. Of the 24 patients with suspected EIA who were referred for rheumatological assessment, 7 were subsequently diagnosed with EIA (one seropositive rheumatoid arthritis [RA], three seronegative RA, two unspecified IA, one reactive arthritis) with a median (range) time from MSUS request to rheumatology referral of 36 (-5 - 58) days. None of the 4 patients referred from the non-EIA group were diagnosed with an inflammatory arthritis. Conclusion: MSUS is widely used by GPs within our region for the assessment of suspected EIA, despite local and national guidelines supporting referral without imaging within 3 days of presentation. Furthermore, we show evidence that GPs interpret scan reports within the individual patient clinical context, with rheumatology referral less likely where the clinical suspicion of EIA is low. Normal MSUS findings contributed to avoidance of referral in 56/87 (64%) of suspected EIA cases, substantially reducing EIA referrals to secondary care. However, MSUS requests within primary care also contributed towards a delay in referral for a small number of patients with confirmed EIA, which we plan to address by signposting to local EIA referral guidelines within the radiology request system. A prospective study of MSUS in the triaging of EIA referrals to secondary care, combined with a qualitative study of the impact of MSUS on GP decision making, are warranted to better understand the potential impact of MSUS in the primary care setting for improved patient care and resource allocation. Disclosures: K.F. Baker None. E. Fatone None. J. Hamilton None.